What are the Consequences of Incorrect Handling in the Treatment of Blunt-Cut Lip Injuries? - Momesso, Gustavo Antonio Correa; De Almeida, Thiago Lopes; Da Silva, William Phillip Pereira [UNESP]; Marão, Heloísa Fonseca; Bassi, Ana Paula Farnezi [UNESP]; Garcia-Júnior, Idelmo Rangel [UNESP]; Faverani, Leonardo Perez [UNESP] (Wolters Kluwer, 2023)
This study aimed report two cases of blunt-cut lip injury which occurred in postoperatory dehiscence. Patients were referred to the emergence attendance and the clinical examination revealed extensive laceration on the upper and lower lips of both patients, highly contaminated with asphalt residue. The affected regions were properly cleaned with saline and antiseptic solution, and, under local anesthesia, suturing was performed in layers in the muscle and oral mucosa region with 4-0 resorbable thread and in the skin region with 6-0 non-absorbable thread. Patients presented different levels of dehiscence on post-operatory evaluation. Thus, it was prescribed antibiotic and healing ointments for decontamination and improvement of the healing process. Third days post-operatory one of the patients presented a great healing of external lips and vermilion lip. However, the other patient presented aesthetic sequelae in the vermilion region of the lip, with a line of fibrosis and misalignment in the region, but not function sequelae. Thus, it was concluded that blunt injuries on the lip must strictly follow the established treatment protocols and must begin aiming for favorable results in the first intervention. Moreover, the postoperative care of the patient and the surgeon are as important as the procedure itself.
Keywords: Lacerations; Suture techniques; Traffic Accidents